Riyadlah Dzikir, Al-Qur’an dan Praktik Garapan Jama’ah Darul Iman Purwakarta - Mustofa, Badrun; Fitriana, Muhammad Azizan; Shofia , Siti (Universitas Islam Tribakti Lirboyo Kediri, 2024)
The prevalence of mental and psychological issues among Muslims is often attributed to their lack of remembrance of God. Riyadlah dhikr, as a spiritual practice aimed at remembering God, is considered a pivotal solution to this issue. Despite various forms of dhikr being practiced across the archipelago, the specific utilization of Qur'anic verses in Riyadhoh dhikr remains underexplored. This study investigates the impact of Riyadhoh dhikr practices using Qur'anic verses, referred to as